Pendidikan moral untuk meminimalisasi penyalahgunaan teknologi - Sabrina, Vina Nurin (Maliki Interdisciplinary Journal, 2023)
The existence of technology can make human life easier. Therefore, current technological developments cannot simply be avoided. However, not all information can be received and understood by children well. The role of parents is really needed here. Parents must educate their children with moral education based on the Qur’an, because family education is one of the first and most important education in human life. The role of the family is to be a vehicle that can fulfill various needs, creating individuals who can adapt well to their environment. The family is the first form of natural education, preparing oneself through the levels of development to face life from childhood to adulthood. Therefore, families must maintain harmony to maintain the continuity of family education so that children receive education directly from their parents for a better future.